2022
DOI: 10.3390/gels8070423
|View full text |Cite
|
Sign up to set email alerts
|

Research Advances of Injectable Functional Hydrogel Materials in the Treatment of Myocardial Infarction

Abstract: Myocardial infarction (MI) has become one of the serious diseases threatening human life and health. However, traditional treatment methods for MI have some limitations, such as irreversible myocardial necrosis and cardiac dysfunction. Fortunately, recent endeavors have shown that hydrogel materials can effectively prevent negative remodeling of the heart and improve the heart function and long-term prognosis of patients with MI due to their good biocompatibility, mechanical properties, and electrical conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 204 publications
0
8
0
Order By: Relevance
“…128 In addition, hydrogel injection alone can reduce oxidative stress, increase myocardial conductivity, and inhibit metalloproteinase-induced malignant remodeling, thereby treating cardiovascular disease. 129 Exosomes or hydrogels alone have been administered to treat cardiovascular diseases with good therapeutic effects. In practical application, exosome is primarily administered intravenously.…”
Section: Combination Therapymentioning
confidence: 99%
“…128 In addition, hydrogel injection alone can reduce oxidative stress, increase myocardial conductivity, and inhibit metalloproteinase-induced malignant remodeling, thereby treating cardiovascular disease. 129 Exosomes or hydrogels alone have been administered to treat cardiovascular diseases with good therapeutic effects. In practical application, exosome is primarily administered intravenously.…”
Section: Combination Therapymentioning
confidence: 99%
“…Current treatments for MI include pharmaceutical therapy, medical device implants, and organ transplants; however, each has its own inherent limitations. Injectable hydrogels have emerged as a promising translational therapeutic toward regeneration of cardiac tissue after MI. These hydrogels have the capacity to encapsulate cells and/or locally release therapeutics after injection through a syringe or catheter. , Several formulations for injection into cardiac tissue have been demonstrated as safe in animals and are in clinical trials. , Recent hydrogels engineered for cardiac tissue to reverse the adverse myocardial microenvironment include matrix metalloproteinase-responsive hydrogels, reactive oxygen species-scavenging hydrogels, and immunomodulatory hydrogels .…”
Section: Introductionmentioning
confidence: 99%
“…The injection of natural or synthetic hydrogel materials into the ventricular wall has become an excellent therapeutic strategy to break the stress feedback pathway, as it reduces the stress load on the ventricular wall by increasing the thickness of the ventricular wall and reshaping the left ventricular geometry, providing mechanical support to the myocardial area and promoting myocardial tissue repair ( 9 - 13 ). A clinical trial of alginate-hydrogel injection treatment was shown to have a good therapeutic effect and the therapeutic potential to inhibit the damage process after MI, and the safety of hydrogel materials injection has also been validated in several clinical trials ( 14 - 18 ).…”
Section: Introductionmentioning
confidence: 99%